The Use of Artificial Intelligence-Based Learning Tools to Enhance Students’ Employment Readiness in the Digital Age - Ayu Gede Willdahlia; Desak Made Dwi Utami Putra; Aniek Suryanti Kusuma; Ni Kadek Nita Noviani Pande (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
This study examines the utilization of Artificial Intelligence (AI)-based learning tools, such as ChatGPT, Grammarly, and Quillbot, in improving student employability in the digital era. The rapid development of technology has brought significant transformation to the education sector, where graduates are now required to possess a broader range of skills beyond academic knowledge, including critical thinking, communication, collaboration, and digital literacy. This research addresses the existing gap between the use of AI as a technical aid and its potential to systematically develop these essential competencies. A quantitative research approach was employed with a purposive sample of 150 active students from the Indonesian Business and Technology Institute (INSTIKI) who actively use AI tools in their academic activities. Data was collected via a Likert-scale online questionnaire and analyzed using descriptive and inferential statistics, including correlation and simple linear regression. The findings indicate that students frequently use AI tools and perceive them as beneficial to their learning process. Overall, the analysis reveals that the use of these AI tools has a positive correlation with students’ employability. The strategic integration of AI serves as a catalyst for fostering skills highly relevant to the demands of the modern job market, particularly in digital literacy, critical thinking, and collaboration. The study concludes that AI is not merely a technical tool, but a strategic partner in holistically preparing students for future professional challenges.